Unveiling Carbon Disclosure: Strategy, Innovation, and Governance - Nola Fajar Arum; Aida Nahar (Jurnal Proaksi, 2026)
Main Purpose - This study aims to investigate the effect of green innovation, green strategy, and firm governance structure on carbon emission disclosure in the renewable energy sector in Indonesia. Method - This study uses a quantitative approach by secondary data from the annual reports of renewable energy companies listed on the IDX. The data was selected using purposive sampling and then processed using SPSS 30 to describe the characteristics of the data and assess the influence of the research variables.Main Findings - The results indicate that firm governance structure does not significantly affect carbon emission disclosure, while green innovation and green strategy positively influence the level of disclosure.Theory and Practical Implications - The study enhances carbon disclosure theory by demonstrating the role of green strategy and innovation in strengthening environmental transparency and supporting Indonesia’s net-zero commitment. Practically, the findings highlight the need for companies to reinforce sustainability strategies and green initiatives to improve disclosure quality.Novelty – This study contributes to carbon emission disclosure research by focusing on renewable energy companies listed on the Indonesia Stock Exchange during the post-pandemic and regulatory transition period of 2019-2024. This study analysis green innovation, green strategy, and firm governance structure using a CDP-based carbon emission disclosure index adapted to the Indonesian regulatory context, making it relevant for developing countries.